Glioblastoma at the crossroads: current understanding and future therapeutic horizons - Shilpi Singh; Devanjan Dey; Debashis Barik; Iteeshree Mohapatra; Stefan Kim; Mayur Sharma; Sujata Prasad; Peize Wang; Amar Singh; Gatikrushna Singh (Signal Transduction and Targeted Therapy)
Abstract Glioblastoma (GBM) remains the most aggressive and lethal brain tumor in adults and poses significant challenges to patient survival. This review provides a comprehensive exploration of the molecular and genetic landscape of GBM, focusing on key oncogenic drivers, such as epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor (PDGFR), and the PI3K/AKT/mTOR pathway, which are critical for tumorigenesis and progression. We delve into the role of epigenetic alterations, including DNA methylation and histone modifications, in driving therapy resistance and tumor evolution. The tumor microenvironment is known for its pivotal role in immune evasion, with tumor-associated macrophages, myeloid-derived suppressor cells, and regulatory T cells creating an immunosuppressive niche that sustains GBM growth. Emerging therapies, such as immunotherapies, oncolytic viral therapies, extracellular vesicle-based approaches, and non-coding RNA interventions, are highlighted as promising avenues to disrupt GBM pathogenesis. Advances in precision medicine and innovative technologies, including electric field therapy and locoregional treatments, are discussed for their potential to overcome the blood‒brain barrier and treatment resistance. Additionally, this review underscores the importance of metabolic reprogramming, particularly hypoxia-driven adaptations and altered lipid metabolism, in fueling GBM progression and influencing the therapeutic response. The role of glioma stem cells in tumor recurrence and resistance is also emphasized, highlighting the need for targeted therapeutic approaches. By integrating molecular targeting, immune energetics, and technological advancements, this review outlines a multidisciplinary framework for improving GBM treatment outcomes. Ultimately, the convergence of genetic, metabolic, and immune-based strategies offers transformative potential in GBM management, paving the way for increased patient survival and quality of life.